2018
DOI: 10.1021/acs.cgd.8b00299
|View full text |Cite
|
Sign up to set email alerts
|

Nitridation of Sapphire as a Precursor to GaN Growth: Structure and Chemistry

Abstract: Nitridation of sapphire substrates is used as a precursor to the growth of GaN films to provide a wetting layer which is closer in terms of structure and chemistry to the overlayer. Nitridation has been carried out by metal–organic chemical vapor deposition at 530, 800, and 1100 °C in an environment of NH3 and H2. The structure and chemistry of the nitrided layer grown at these different temperatures have been studied by X-ray photoelectron spectroscopy, electron diffraction, high resolution electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…At present, GaN is widely used in LEDs. 59 The outstanding material properties of GaN can be optimally exploited in its monocrystalline form, and therefore in LEDs, it is grown epitaxially on specific substrates, usually on sapphire. 10 In parallel, studies on perfecting the epitaxial growth of crystalline GaN films on Si are pursued to enable the use of the low-cost mature Si technology and the higher electronic and thermal conductivity of Si.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, GaN is widely used in LEDs. 59 The outstanding material properties of GaN can be optimally exploited in its monocrystalline form, and therefore in LEDs, it is grown epitaxially on specific substrates, usually on sapphire. 10 In parallel, studies on perfecting the epitaxial growth of crystalline GaN films on Si are pursued to enable the use of the low-cost mature Si technology and the higher electronic and thermal conductivity of Si.…”
Section: Introductionmentioning
confidence: 99%
“…At present, GaN is widely used in LEDs. The outstanding material properties of GaN can be optimally exploited in its monocrystalline form, and therefore in LEDs, it is grown epitaxially on specific substrates, usually on sapphire . In parallel, studies on perfecting the epitaxial growth of crystalline GaN films on Si are pursued to enable the use of the low-cost mature Si technology and the higher electronic and thermal conductivity of Si. , The growth of high-quality monocrystalline GaN on Si substrate suffers from several problems (melt-back etching, large lattice mismatch, and creation of a large tensile stress postgrowth), which deteriorate the quality of GaN and ultimately the device performance. ,, …”
Section: Introductionmentioning
confidence: 99%
“…33 The peak shift might be caused by a high density of Al vacancies in the layer. 34 Interestingly, the N–O component with a binding energy of (398.5–399.9 eV) 33,35 expected for AlNO x complexes is absent, indicating that the surface is fully covered by an AlN layer.…”
Section: Resultsmentioning
confidence: 99%
“…Several procedures have been presented using different synthesis methods in GaN production, aiming for the reduction of crystalline mismatch between the material and substrate. On the one hand, Amano et al reported the use of an AlN film as a buffer layer for obtaining high-quality GaN films. Furthermore, the obtention of crystalline GaN was successfully accomplished by the two-step growth method, by depositing a low-temperature GaN film as a buffer layer to support the growth of the main film .…”
Section: Introductionmentioning
confidence: 99%